The potential distribution area and dynamic niche variation analysis of an alien invasive plant Senecio vulgaris L - Enxiang Zhang; Xinshuai Wang; Bo Lei; Yongwei Han; Jun Sun (Scientific Reports)
Abstract Senecio vulgaris L. (Asteraceae), a European-origin invasive plant, has established widespread populations in China since the nineteenth century, posing both ecological and health-related threats due to its herbicide resistance, toxic pyrrolizidine alkaloids, and broad habitat adaptability. Despite being classified as a Level 4 invasive species in China, its potential risk remains underestimated. In this study, we applied an optimized MaxEnt model using occurrence data from both native (Europe) and invasive (China) ranges to predict the species’ potential distribution. Our results revealed high environmental suitability in central, eastern, southwestern, and northeastern China, with human activity, temperature, and precipitation as dominant predictors. Niche analysis indicated that S. vulgaris in China occupies environmental conditions largely overlapping with its native niche, demonstrating niche conservatism rather than expansion. These findings suggest that even moderately ranked invasive species can maintain ecological stability while gradually expanding, especially under increasing anthropogenic pressure. Our results underscore the need for targeted monitoring and preemptive management in agriculturally sensitive regions. This study provides a practical framework for assessing and managing adaptable invasive plants beyond those classified as high risk.